Therapeutic and Diagnostic Nanomaterials - Devasena T.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2017)
This brief highlights nanoparticles used in the diagnosis and treatment of prominent diseases and toxic conditions. Ecofriendly methods which are ideal for the synthesis of medicinally valued nanoparticles are explained and the characteristic features of these particles projected. The role of these particles in the therapeutic field, and the induced biological changes in some diseases are discussed. The main focus is on inflammation, oxidative stress and cellular membrane integrity alterations. The effect of nanoparticles on these changes produced by various agents are highlighted using in vitro and in vivo models. The mechanism of nanoparticles in ameliorating the biological changes is supported by relevant images and data. Finally, the brief demonstrates recent developments on the use of nanoparticles in diagnosis or sensing of some biological materials and biologically hazardous environmental materials.
Diagnostic and therapeutic nanomaterials -- Multifunctional Nanoparticles -- Biomarkers -- Diagnostic and therapeutic Techniques -- Toxicity and risk assessment -- In vitro and in vivo applications of selected nanomaterials.
Keywords: Biomedical engineering; Biomaterials; Medicine -- Research; Biology -- Research; Microtechnology; Microelectromechanical systems; Clinical biochemistry; Biotechnology; Biomedical Engineering and Bioengineering; Biomaterials; Biomedical Research; Microsystems and MEMS; Medical Biochemistry; Chemical Bioengineering